1976
DOI: 10.1038/ki.1976.125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 25-hydroxycholecalciferol on bone lesions of children with terminal renal failure

Abstract: Quantitative histology was performed on serial iliac crest biopsies obtained from 14 children with terminal renal failure. A long-term study on the comparative effects of vitamin D2 and 25-hydroxycholecalciferol [25-(OH)D3], in five patients with severe lesions of osteomalacia and/or osteitis fibrosa, demonstrated the efficiency of 25 to 200 mug/day of 25-(OH)D3 and the lack of therapeutic action of 345 to 685 mug/day of vitamin D2. In nine subjects with normal roentgenograms or minimal skeletal alterations, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Although the relationship between vitamin D and bone is well established in treatment studies (18)(19)(20)(21), the actual handling of the different vitamin D metabolites by bone has not been clarified. Most studies on this topic have been performed in either animals with vitamin D deficiency or in fetal cell preparations often from the rat calvaria (1-3, 7, 8).…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between vitamin D and bone is well established in treatment studies (18)(19)(20)(21), the actual handling of the different vitamin D metabolites by bone has not been clarified. Most studies on this topic have been performed in either animals with vitamin D deficiency or in fetal cell preparations often from the rat calvaria (1-3, 7, 8).…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that large doses of vitamin D [17] and 25-OHD.t [15,18,19] are able to improve the uraemic bone lesions in patients with re maining kidney tissue. This might be due to an increased production of l,25-(OH)aD3 induced by a mass action effect of 25-OHÜ3 on the I-hydroxylase system in the damaged kidney, or perhaps on the production of other vitamin D metabolites such as 24,25-dihydroxycholecalciferol.…”
Section: Discussionmentioning
confidence: 99%
“…However, Witer et al (1976) reported that in a non-dialysed girl (14 years of age) with chronic renal failure, 13,000-28,000 IU/day of VD2 supplementation for 5 months were not effective for the correction of hypocalcemia and renal bone diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Major symptoms related to these abnormal calcium metabolism in long-term dialysis are as follows: osteomalacia, and other complications of secondary hyperpara thyroidism (hypercalcemia, metastatic calcification, and pruiritis). It is well recognized that these abnormal calcium metabolism is primarily due to defective formation of 1, 25 We have treated patients by hemodialysis using dialysate containing a fixed calcium concentration (3.5 mEq/liter) since 1972. To correct negative calcium balance in patients on chronic hemodialysis, VD2 has been used in our hemodialysis unit.…”
Section: Discussionmentioning
confidence: 99%